Formulation, Characterization and Antioxidant Myricetin Nanophytosome for Topical Delivery - Aini, Purnamasari Nur; Muhammad, Dzakwan; Eko, Pramukantoro Ganet; Rachmat, Mauludin; Fahmi, El (Asian Journal of Pharmaceutical Research and Development, 2020)
Background: Phytosomes are recently introduced drug delivery system and novel botanical formulation to produce lipophilic molecular complex to improve absorption and bioavailability of phytoconstituent. Myricetin is a well-known flavonoid with different biological effects and contributed in food preserving by free radical scavenging activity. However, bioavailability of myricetin is an important limiting factor for its antioxidant activities. Purpose: To overcome this limitation, in the present study we aimed to produce myricetin-loaded nano phytosomes to improve its physicochemical stability and bioavailability. Methods: myricetin-loaded nano phytosome was prepared by using phosphatidylcholine (PC) and cholesterol (CH). Myricetin nanophytosomes system was characterized by particle size analyzer, particle size distribution (PDI), encapsulation efficiency and potential antioxidant activity. Results: Results showed that formulation with the myricetin: PC: CH molar ratio of 1: 2: 0.8 had lower particle size (291.11 nm) and higher encapsulation efficiency percent (93%). Morphology analysis showed that myricetin nanophytosome spherical shape. The potential antioxidant data showed that incorporation myricetin in the phospholipid myricetin remained unchanged even after encapsulation of myricetin in binarynanophytosome formulation. Conclusion: Nano phytosomal formulation of myricetin showed promising potential in fortification of nutraceutical with water insoluble antioxidants.